The Belt and Road Initiative Green Development Case Studies Report 2020 (Springer Nature, 2022)
This is an Open Access book. In accordance with the 2030 Agenda for Sustainable Development, it showcases 17 projects under the framework of Belt & Road Initiative (BRI). These projects cover ninefields, namely, biodiversity and ecosystem, clean energy, clean water, sustainable transportation, solid waste treatment, sustainable consumption and production, green buildings, sustainable foodproduction and corporate social responsibility. Aiming at achieving green development, these projects, in their implementation, adhere to the concept of ecological civilization, combine China's strict environmental protection systems and international standards, and take various measures of environmental protection based on the conditions of the local environment. These measures include joint efforts with local governments, businesses and communities, optimizating of design and construction plans, strict controling over different types of pollutants, and in situ conservation of species and ecosystems.The experience and practice of these 13 projects set an example for the latecomers.